Molecularly Imprinted Polymer Basedmicro-Solid Phase Extraction Of Bisphenol A And Sulfonamide Antiobiotics In Aqueous Samples - Rozaini, Muhammad Nur’ Hafiz (2018)
This thesis focuses on the development, validation and application of new sample preparation methods for the determination of bisphenol A (BPA) and sulfonamide antibiotics (SAs) in aqueous matrices. A rapid microextraction method based on ultrasound-assisted emulsification micro-solid phase extraction incorporated with molecularly imprinted polymer (USAE-MIP-μ-SPE) was developed for the determination of BPA in water, beverages and the aqueous liquid in canned foods prior to high performance liquid chromatography diode array detector (HPLC-DAD).